2008
DOI: 10.1063/1.2894723
|View full text |Cite
|
Sign up to set email alerts
|

Quantum efficiency of ambipolar light-emitting polymer field-effect transistors

Abstract: The emission characteristics and external quantum efficiencies of ambipolar polymer light-emitting field-effect transistors are investigated as a function of applied voltage, current density, and ratio of hole to electron mobility. Green-emitting poly(9,9-di-n-octylfluorene-alt-benzothiadiazole) (F8BT) with balanced electron and hole mobilities and red-emitting poly((9,9-dioctylfluorene)-2,7- diyl-alt-[4,7-bis(3-hexylthien-5-yl)-2,1,3-benzothiadiazole]-2′,2″-diyl) (F8TBT) with strongly unbalanced hole and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 35 publications
3
103
0
Order By: Relevance
“…45 Several studies have indicated that for organic semiconductor materials the EL singlet formation probability is close to 1/4, the quantum-statistical value. [52][53][54][55] However, it has been argued from other studies that it can be strongly enhanced, in particular in polymers. [56][57][58][59][60][61][62][63][64] For poly-phenylene-vinylene (PPV) based polymers, e.g., the singlet fraction as obtained using various methods ranges from approximately 20% (Ref.…”
Section: -mentioning
confidence: 88%
“…45 Several studies have indicated that for organic semiconductor materials the EL singlet formation probability is close to 1/4, the quantum-statistical value. [52][53][54][55] However, it has been argued from other studies that it can be strongly enhanced, in particular in polymers. [56][57][58][59][60][61][62][63][64] For poly-phenylene-vinylene (PPV) based polymers, e.g., the singlet fraction as obtained using various methods ranges from approximately 20% (Ref.…”
Section: -mentioning
confidence: 88%
“…46 Owing to the relatively large aromatic core of 5, we can expect that both possible products, the major product Br-TBTNidppe-Br 6 and the minor product Br-Nidppe-TBT-Nidppe-Br 7, are formed during the reaction of 5 with NiEt 2 bipy followed by ligand exchange (Scheme 3). Two pairs of doublets with very similar chemical shifts in the 31 P NMR spectrum of the initiator solution point to such a nonequivalent mixture of 6 and 7 (see Figure SI-6). It is important to note that one is still able to determine whether Ni(0)dppe can "ring walk" over the TBT bridge by analyzing the polymeric products.…”
Section: Scheme 1 Mechanism Of F8tbt-br Activation Using Niet 2 Bipymentioning
confidence: 99%
“…3 For example, TBT copolymers with fluorene show ambipolar transport behavior in field-effect transistors 31 and can be used either as p-type 32 or n-type 33 material. In addition, the strong red photoluminescence of conjugated polymers containing TBT units has made such materials interesting candidates for light-emitting devices.…”
mentioning
confidence: 99%
“…[24] An order of magnitude lower electron mobility for F8TBT compared to F8BT is also calculated from transistor characteristics. [25] Given that P3HT:F8TBT blends can achieve reasonable efficiencies despite the relatively poor electron mobility of F8TBT, the origin of the poor efficiency of P3HT:F8BT blends is worth reexamining. Figure 9 presents the device characteristics of 1:1 P3HT:F8BT blends.…”
Section: P3ht:f8bt Blendsmentioning
confidence: 99%